Multilevel Analysis on the Determinants of Overweight among Children Under Five in Kediri, East Java - Khalifatunisak, Alfadefi; Salimo, Harsono; Dewi, Yulia Lanti Retno (Journal of Maternal and Child Health, 2018)
Background: Child overweight and obesity are an important public health issue worldwide. Overweight and obese children are likely to stay obese into adulthood and more likely to develop non-communicable diseases like diabetes and cardiovascular diseases. This study aimed to determine factors associated with overweight among children under five in Kediri, East Java, using a multilevel analysis model.Subjects and Method: This was a case control study conducted at 25 posyandus (integrated family health posts) in Kediri, East Java, from April to May 2018. A sample of 200 children under five was selected by fixed disease sampling. Posyandu was selected by stratified random sampling. Children were located at level 1 and posyandu at level 2 in the multilevel analysis model. The dependent variable was overweight. The independent variables were maternal body mass index (BMI), exclusive breastfeeding, calorie intake, feeding pattern, and nutritional status monitoring. Overweight status was measured by weight for height z-score. The data were collected by questionnaire and analyzed by a multilevel logistic regression model run in Stata 13.Results: Maternal BMI ?25 (b= 0.72; 95% CI= -0.98 to 1.54; p= 0.085) and calorie intake exceeding the recommended allowance (b= 1.45; 95% CI= 0.59 to 2.31; p= 0.001) increased the risk of overweight in children under five. Good feeding pattern (b= -1.11; 95% CI= -2.15 to -0.08; p= 0.034), exclusive breastfeeding (b= -0.97; 95% CI= -1.98 to 0.02; p= 0.057), and regular nutritional status monitoring (b= -4.34; 95% CI= -6.42 to -2.21; p<0.001) decreased the risk of overweight. Posyandu showed negligible contextual effect on the incidence of child overweight with ICC= 0.98%.Conclusion: Maternal BMI ?25 and calorie intake exceeding the recommended allowance increase the risk of overweight in children under five. Good feeding pattern, exclusive breastfeeding, and regular nutritional status monitoring decrease the risk of overweight in children under five. Posyandu has a negligible contextual effect on child overweight.Keywords: overweight, children under five, exclusive breastfeeding, maternal body mass index, multilevel analysisCorrespondence:Alfadefi Khaliatunnisak. Masters Program in Public Health, Universitas Sebelas Maret, Jl. Ir. Sutami 36 A, Surakarta 57126, Central Java. Email: emailealfadefi999@gmail.com.Journal of Maternal and Child Health (2018), 3(4): 261-268https://doi.org/10.26911/thejmch.2018.03.04.03